2003
DOI: 10.1002/jcb.10606
|View full text |Cite
|
Sign up to set email alerts
|

Integrative nuclear FGFR1 signaling (INFS) as a part of a universal “feed‐forward‐and‐gate” signaling module that controls cell growth and differentiation

Abstract: A novel signaling mechanism is described through which extracellular signals and intracellular signaling pathways regulate proliferation, growth, differentiation, and other functions of cells in the nervous system. Upon cell stimulation, fibroblast growth factor receptor-1 (FGFR1), a typically plasma membrane-associated protein, is released from ER membranes into the cytosol and translocates to the cell nucleus by an importin-beta-mediated transport pathway along with its ligand, FGF-2. The nuclear accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
149
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 104 publications
(292 reference statements)
13
149
0
Order By: Relevance
“…The inhibition of BrdUrd incorporation into the cells in SVZ and in rostral migratory stream by transfected FGFR1(SP-͞NLS) observed in the present study demonstrates that the nuclear receptor controls the proliferation of the NSPCs in situ. These findings are consistent with our previous in vitro studies that showed that FGFR1(SP-͞NLS) induces the neural progenitor cells' withdrawal from the cell cycle and initiates differentiation (46,57). Thus, ORMOSIL-mediated in vivo transfection of the SVZ cells provides an effective means for elucidating the biology of stem͞progenitor cells, allowing for the modification of these developing cells for therapeutic manipulations.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The inhibition of BrdUrd incorporation into the cells in SVZ and in rostral migratory stream by transfected FGFR1(SP-͞NLS) observed in the present study demonstrates that the nuclear receptor controls the proliferation of the NSPCs in situ. These findings are consistent with our previous in vitro studies that showed that FGFR1(SP-͞NLS) induces the neural progenitor cells' withdrawal from the cell cycle and initiates differentiation (46,57). Thus, ORMOSIL-mediated in vivo transfection of the SVZ cells provides an effective means for elucidating the biology of stem͞progenitor cells, allowing for the modification of these developing cells for therapeutic manipulations.…”
Section: Discussionsupporting
confidence: 81%
“…In cultured cells and in the developing rat brain, FGFR1 was associated with the peripheral cytoplasm but also with the cell nuclei (46,47). The cell-surface FGFR mediates the mitogenic effects of extracellular FGFs, whereas the nonmembrane nuclear FGFR1 signals withdrawal from the cell cycle and postmitotic growth (46). FGFR1(SP-͞NLS), which does not associate with cell membranes and is expressed specifically in the nucleus, has been shown to stimulate differentiation of human neural progenitor cells in vitro and to directly inf luence gene activities without affecting the cell survival (28, 36, 48 -55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear accumulation of FGFR1 and FGF-2 were observed in different laboratories in developing brain, neurons, astrocytes, adrenal medullary cells, and fibroblasts (10). Nuclear accumulation of FGFR1 accompanied growth of astrocytes and glioma cells (11,14,19), neurons (19), differentiation of neuronal progenitor cells (21), and functional adaptations of adrenal medullary cells (12,13,20), which were prevented by transfection of the cytoplasmic/nuclear dominant negative FGFR1(TKϪ), or its exclusively nuclear derivative in which the signal peptide (SP) was replaced by an NLS.…”
mentioning
confidence: 95%
“…Studies in this and other laboratories have shown that upon cell stimulation, FGFR1, a typically plasma membrane-associated protein, translocates to the cell nucleus along with nonsecreted, intracellular forms of FGF-2, which lack a signal peptide but contain a functional nuclear localization signal (NLS) (10). Nuclear FGFR1 is full-length, binds FGF-2, and has an active TK domain (11,12).…”
mentioning
confidence: 99%